Juridical analysis of the effectiveness of the investigation of Sailing Approval (SPB) violations at the Ditpolairud Riau Islands Police - Ibrahim Sembiring; Fadlan Fadlan; Sayid Fadhil; Soerya Respationo; Siti Nurkhotijah (Dynamics of Politics and Democracy, 2025)
Purpose: This study analyzes the effectiveness of investigations into Sailing Approval (SPB) violations conducted by the Ditpolairud Riau Islands Police. It seeks to evaluate how well current law enforcement mechanisms ensure maritime safety and legal compliance under the Navigation Law. Research methodology: The research employs a normative and empirical juridical approach. Data were collected from legislation, literature reviews, and in-depth interviews with investigators, Syahbandar officials, and maritime business operators. The findings were validated through triangulation and analyzed descriptively using John Rawls’ Theory of Justice, Friedman’s Legal System Theory, and Sudikno Mertokusumo’s Legal Certainty Theory. Results: Investigations into SPB violations have been carried out in accordance with legal procedures, including coordination between Ditpolairud, Syahbandar, PPNS, and prosecutors. While enforcement actions have increased compliance, several challenges remain, such as limited resources, overlapping authority, legal gaps, maladministration, and low awareness among shipowners and fishermen. Digitalization of SPB documents and improved transparency in service fees were identified as key solutions. Conclusions: The investigations are generally effective but still constrained by structural, substantial, and cultural barriers. Effective enforcement requires harmonized regulations, institutional synergy, technological integration, and public legal awareness to ensure maritime safety and compliance. Limitations: This study is limited to the jurisdiction of the Riau Islands and relies on qualitative field interviews, without quantitative assessment of enforcement outcomes. Contribution: The study contributes to maritime law by emphasizing justice, legal certainty, and system effectiveness in SPB investigations, while offering recommendations to improve institutional capacity, transparency, and regulatory alignment.